2016
DOI: 10.1111/jfbc.12314
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Extraction of Rice Bran Protein Using Response Surface Methodology

Abstract: Rice bran was used for isolating protein through ultrasonic‐assisted extraction. The protein was converted into protein hydrolysates (PH) with three commercial enzymes. The optimal condition for rice bran protein production was 76% sonication amplitude, 18 min extraction and 0.99 g/10 mL solid–liquid ratio, which gave protein yield of 4.73 ± 0.03%. The degree of hydrolysis for the rice bran protein by Subtilisin A (SPH), Actinase E (APH) and Neutrase 0.8L (NPH) was 20.03 ± 0.24%, 13.84 ± 0.04% and 5.54 ± 0.07%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
1
19
1
2
Order By: Relevance
“…However, only few studies applied in vitro GI digestion to stimulate antioxidant activity of rice bran protein. Mostly, the nonpurified rice bran protein hydrolysates were directly used to determine its bioactivity (Phongthai et al, ; Thamnarathip et al, ; Wattanasiritham et al, ); meanwhile, the purification of those mix peptides by using chromatography techniques has never been reported. According to our previous study (Phongthai, D'Amico, Schoenlechner, & Rawdkuen, ), it was clearly seen that total aromatic amino acid content in nonpurified rice bran protein hydrolysates had a strong positive correlation with free radicals scavenging activity and reducing power (Pearson's correlation coefficients; r > .83).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only few studies applied in vitro GI digestion to stimulate antioxidant activity of rice bran protein. Mostly, the nonpurified rice bran protein hydrolysates were directly used to determine its bioactivity (Phongthai et al, ; Thamnarathip et al, ; Wattanasiritham et al, ); meanwhile, the purification of those mix peptides by using chromatography techniques has never been reported. According to our previous study (Phongthai, D'Amico, Schoenlechner, & Rawdkuen, ), it was clearly seen that total aromatic amino acid content in nonpurified rice bran protein hydrolysates had a strong positive correlation with free radicals scavenging activity and reducing power (Pearson's correlation coefficients; r > .83).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic hydrolysis is usually chosen to expose and release some active peptides from various protein sources. The hydrolysis of rice bran protein with actinase and neutrase (Phongthai, Lim, & Rawdkuen, 2016b), trypsin (Wang et al, 2017), and alcalase (Thamnarathip, Jangchud, Nitisinprasert, & Vardhanabhuti, 2016) was previously studied. Peptide bonds in the polypeptide chain can be enzymatically hydrolyzed in order to create a range of oligopeptides with different molecular weight and/or amino acid sequences that provide a diverse activity.…”
mentioning
confidence: 99%
“…A Previous study reported that BSG particle size has a significant effect on the separation and structure of arabinoxylans from BSG (Reis et al, 2015). Several studies reported that ultrasound pretreatment improved protein separation from agricultural products such as rice bran (Phongthai et al, 2016), defatted soy flakes (Karki et al, 2010) and olive kernels (Rosell o-Soto et al, 2015). To date and to our best knowledge, no study has reported using ultrasonication to improve the enzymatic separation of protein from BSG and characterise the properties of protein produced from the ultrasound-assisted enzymatic extraction.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the restricted functional properties of the native protein, leading to poor bread quality. However, in some reported studies it was discovered that the functional properties of protein can be effectively modified and extended by enzymatic hydrolysis [ 6 , 7 , 8 ], resulting in a wider range of applications. Therefore, the use of protein hydrolysates to improve bread quality may be useful for the development of high-quality gluten-free bread.…”
Section: Introductionmentioning
confidence: 99%